Filtering membrane, preparation method thereof and filtering device

By using spinel material to form a multi-layer structure in the ceramic filter membrane, the problems of insufficient mechanical strength and low porosity of the ceramic filter membrane are solved, and good filtration performance and mechanical performance are achieved.

CN119746652APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411105646.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing ceramic filter membranes have problems such as insufficient mechanical strength, large pore distribution and low porosity, which affects its filtration performance and service life.

Method used

The support layer, intermediate layer and filter layer of the filter membrane are formed by spinel material, and a multi-layer structure is formed through the sintering process. The arrangement of the intermediate layer and support layer ensures that the porosity of the filter layer is smaller than that of the intermediate layer, thereby improving the filtering performance and mechanical properties.

Benefits of technology

The good filtration performance and mechanical properties of the ceramic filter membrane are achieved, reducing costs, and improving the pore-forming performance and service life of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746652A_ABST
    Figure CN119746652A_ABST
Patent Text Reader

Abstract

The invention provides a filtering membrane, a preparation method thereof and a filtering device. The filtering membrane comprises a supporting layer, a middle layer and a filtering layer. The middle layer is arranged on the surface of one side of the supporting layer in the thickness direction and comprises a spinel material. The filtering layer is arranged on the surface of the side, away from the supporting layer, of the middle layer and comprises spinel materials, and the porosity of the filtering layer is smaller than that of the middle layer. According to the filtering membrane, the filtering layer and the middle layer are made of the spinel material, the cost is low, the pore-forming performance is good, the middle layer can prevent powder in the filtering layer from blocking the supporting layer, and the filtering layer has good filtering performance and good mechanical performance due to the arrangement of the middle layer and the supporting layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application generally relates to the technical field of filter membranes, and more specifically to a filter membrane and a preparation method thereof, and a filter device. Background Art

[0002] At present, separation membranes can be mainly divided into two categories: organic separation membranes and inorganic separation membranes. Among them, the porous structure ceramic filter membranes belonging to the latter have a series of advantages such as high strength, stable physical and chemical properties, excellent thermal stability, corrosion resistance, etc., and are widely used in automobile exhaust purification, catalyst carriers, building noise reduction, industrial wastewater filtration and other fields. However, the ceramic filter membranes in the prior art still have problems such as insufficient mechanical strength, large pore distribution and too low porosity. Summary of the invention

[0003] A series of simplified concepts are introduced in the Summary of the Invention section, which will be further described in detail in the Detailed Description of the Invention section. The Summary of the Invention section of this application does not mean to attempt to define the key features and essential technical features of the claimed technical solution, nor does it mean to attempt to determine the scope of protection of the claimed technical solution.

[0004] In order to at least partially solve the above problems, the present application provides a filter membrane in a first aspect, the filter membrane comprising:

[0005] Support layer;

[0006] an intermediate layer, the intermediate layer being disposed on one side surface of the support layer in the thickness direction and comprising a spinel material; and

[0007] The filter layer is arranged on a surface of the intermediate layer facing away from the support layer and comprises a spinel material. The porosity of the filter layer is smaller than the porosity of the intermediate layer.

[0008] According to the filter membrane of the first aspect of the present application, the filter layer and the intermediate layer are formed of spinel material, which has low cost and good pore-forming performance. The intermediate layer can prevent the powder in the filter layer from clogging the support layer, and the filter layer has good filtering performance and good mechanical properties due to the arrangement of the intermediate layer and the support layer.

[0009] Optionally, the spinel material of the intermediate layer and / or the filter layer is MgAl2O4.

[0010] Optionally, the filter layer has a thickness of 15 μm to 57 μm.

[0011] Optionally, the filter layer has a thickness of 15 μm to 25 μm.

[0012] Optionally, the support layer comprises an inorganic compound A, and the mass of the inorganic compound A accounts for 55% to 95% of the mass of the support layer.

[0013] Optionally, the inorganic compound A includes one or more of alumina, zirconium dioxide, titanium dioxide and zeolite.

[0014] Optionally, the support layer has a thickness of at least 1.5 mm.

[0015] Optionally, the porosity of the intermediate layer is smaller than the porosity of the support layer.

[0016] Optionally, the thickness of the filter layer is smaller than the thickness of the support layer.

[0017] A second aspect of the present application provides a method for preparing a filtration membrane, comprising:

[0018] S1, sintering the inorganic compound A to form a support layer;

[0019] S2, dip-coating the inorganic compound B and the inorganic compound C onto the support layer and then sintering them, thereby forming an intermediate layer on the surface of the support layer;

[0020] S3, dip-coating the inorganic compound D and the inorganic compound E onto the intermediate layer and then sintering the intermediate layer to form a filter layer on the surface of the intermediate layer.

[0021] According to the method for preparing the filter membrane of the second aspect of the present application, the ceramic membrane prepared through steps S1, S2 and S3 has a support layer, an intermediate layer and a filter layer, so that the filter layer has the support of the support layer and the filter layer, has good mechanical properties, and can also be suitable for large flow and high pressure filtration scenarios when the filter layer thickness is insufficient.

[0022] Optionally, in step S1, step S2 and step S3, the sintering temperature is 1200°C to 1400°C.

[0023] Optionally, the step S1 includes:

[0024] The inorganic compound A, the pore former and the film-forming aid are ball-milled, dried and sieved to obtain a solid powder;

[0025] The support layer is obtained by tableting and sintering the solid powder.

[0026] Optionally, the mass of the inorganic compound B accounts for 40% to 50% of the total mass of the raw material of the intermediate layer, and the mass of the inorganic compound C accounts for 40% to 50% of the total mass of the raw material of the intermediate layer; and / or

[0027] The inorganic compound B includes one or more of α-Al2O3, β-Al2O3, and γ-Al2O3, and the inorganic compound C is Mg5(CO3)4(OH)2·4H2O.

[0028] Optionally, the mass of the inorganic compound D accounts for 70% to 75% of the total mass of the raw material of the filter layer, and the mass of the inorganic compound E accounts for 25% to 30% of the total mass of the raw material of the intermediate layer; and / or

[0029] The inorganic compound D is at least one of α-Al2O3, β-Al2O3, and γ-Al2O3, and the inorganic compound E is MgO.

[0030] A third aspect of the present application provides a filtration device, comprising the filtration membrane according to the above.

[0031] The filtering device according to the third aspect of the present application has low cost, good pore-forming performance, and has good filtering performance as well as good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The following drawings of the embodiments of the present application are hereby used as part of the present application for understanding the present application. The drawings show the embodiments of the present application and their descriptions, and are used to explain the principles of the present application. In the drawings,

[0033] Figure 1 This is a scanning electron microscope image of the filter membrane of the first embodiment of the present application, wherein P1 is an enlarged view of the filter layer, and P2 is an enlarged view of the middle layer;

[0034] Figure 2 This is a scanning electron microscope image of the support layer of the filter membrane of the first embodiment of the present application;

[0035] Figure 3 This is a scanning electron microscope image of the filter membrane of the third embodiment of the present application, wherein P3 is an enlarged view of the filter layer, and P4 is an enlarged view of the intermediate layer;

[0036] Figure 4 This is a scanning electron microscope image of the support layer of the filter membrane according to the third embodiment of the present application. DETAILED DESCRIPTION

[0037] In the following description, a large number of specific details are provided to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application embodiments can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application embodiments, some technical features well known in the art are not described.

[0038] In this document, “equal”, “same”, etc. are not strictly limited in a mathematical and / or geometric sense, but also include errors that can be understood by those skilled in the art and are allowed in manufacturing or use.

[0039] Unless otherwise stated, the numerical ranges herein include not only the entire range within its two endpoints but also include several sub-ranges contained therein.

[0040] The present application provides a filter membrane, which includes a support layer, an intermediate layer and a filter layer. The intermediate layer is arranged on one side surface of the support layer in the thickness direction and includes a spinel material. The filter layer is arranged on one side surface of the intermediate layer away from the support layer and includes a spinel material, and the porosity of the filter layer is less than the porosity of the intermediate layer.

[0041] According to the filter membrane of the present application, the filter layer and the intermediate layer are formed of spinel material, which has low cost and good pore-forming performance. The intermediate layer can prevent the powder in the filter layer from clogging the support layer, and the filter layer has good filtering performance and good mechanical properties due to the arrangement of the intermediate layer and the support layer.

[0042] Optionally, the spinel material of the intermediate layer and the filter layer can be MgAl2O4, which has low cost and good pore-forming performance.

[0043] Optionally, the thickness of the filter layer is between 15 μm and 57 μm, so that the filter layer is not too thick, has a higher filtering accuracy, and can separate smaller substances (such as proteins, high molecular organic matter, bacteria, etc.).

[0044] Preferably, the thickness of the filter layer is 15 μm to 25 μm, so that the filter membrane has good filtering performance.

[0045] Optionally, the porosity of the middle layer is smaller than that of the support layer, so that the porosity of the medium decreases step by step from the support layer through the middle layer to the filter layer, so that the medium is preliminarily filtered by the support layer before passing through the middle layer and the filter layer, thereby realizing multi-stage filtration of the medium, which is beneficial to prolonging the service life of the filter membrane.

[0046] Optionally, the thickness of the filter layer is less than that of the support layer, so that the support layer has good support for the filter layer. Optionally, the thickness of the intermediate layer is greater than that of the filter layer and less than that of the support layer, so as to further ensure support for the filter layer.

[0047] Optionally, the thickness of the support layer is at least 1.5 mm, thereby improving the overall mechanical properties of the filter membrane and making the filter membrane suitable for filtration scenarios with larger flow rates and higher pressures.

[0048] Optionally, the support layer has an inorganic compound A, and the mass of the inorganic compound A accounts for 55% to 95% (e.g., 85%, 70%) of the mass of the support layer, so that the support layer has good mechanical properties and stability. Preferably, the inorganic compound A includes one or more of aluminum oxide, zirconium dioxide, titanium dioxide and zeolite.

[0049] The present application also provides a method for preparing a filtration membrane, comprising:

[0050] S1, using inorganic compound A and pore-forming agent through dry pressing and high-temperature sintering to form a support layer;

[0051] S2, stirring and dip-coating the inorganic compound B and the inorganic compound C onto the support layer and then sintering them to form an intermediate layer on the surface of the support layer;

[0052] S3, the inorganic compound D and the inorganic compound E are stirred and dip-coated onto the intermediate layer and then sintered, thereby forming a filter layer on the surface of the intermediate layer.

[0053] According to the preparation method of the filter membrane of the present application, the ceramic membrane prepared through steps S1, S2 and S3 has a support layer, an intermediate layer and a filter layer, so that the filter layer has the support of the support layer and the filter layer, has good mechanical properties, and can also be suitable for large flow and high pressure filtration scenarios when the filter layer thickness is insufficient.

[0054] Furthermore, in step S1, step S2 and step S3, the sintering temperature is between 1200°C and 1400°C, so that the support layer, the middle layer and the filter layer of the prepared filter membrane have good porosity, thereby making the filter membrane have good filtering performance.

[0055] Step S1 is used to prepare a support layer, and step S1 is first introduced below.

[0056] Preferably, the inorganic compound A is Al2O3.

[0057] Optionally, the particle size of the inorganic compound A is 0.5 μm to 2 μm, and the mass of the inorganic compound A accounts for 60% to 90% of the total mass of the raw material of the support layer, thereby ensuring the porosity and mechanical strength of the support layer.

[0058] Further, step S1 includes:

[0059] S11, adding inorganic compound A, pore former and film-forming aid into a container containing ethanol and zirconium oxide balls, and shaking well to mix;

[0060] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution to 1.5 seconds / revolution;

[0061] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0062] S14, finely sifting the solid powder using a 150-200 mesh sieve;

[0063] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 10 MPa to 12 MPa, and the pressure holding time is 1 minute;

[0064] S16. Sinter at a temperature of 1200° C. to 1400° C. for 2 hours to produce a support layer sample.

[0065] Optionally, in step S1, the pore-forming agent is an organic pore-forming agent, and the particle size of the pore-forming agent is 10 μm to 20 μm, which can form pores in the support layer, further improve the porosity of the support layer, and improve the working efficiency of the filter membrane.

[0066] Optionally, the mass of the pore former accounts for at most 40% of the total mass of the raw material of the support layer, so as to prevent excessive pore former from affecting the mechanical strength of the support layer.

[0067] Optionally, the pore-forming agent includes one of hydroxyethyl methylcellulose, hydroxymethyl cellulose, starch and rice husk. Preferably, the pore-forming agent is corn starch.

[0068] Optionally, in step S1, the film-forming aid is a water-soluble film-forming agent, and the film-forming aid includes one of acrylic copolymer emulsion, PVA aqueous solution (polyvinyl alcohol aqueous solution), and polyvinyl pyrrolidone. Preferably, the film-forming aid is PVA aqueous solution.

[0069] Step S2 is used to prepare the intermediate layer, and step S2 is further introduced below.

[0070] Optionally, in step S2, the particle size of inorganic compound B is 0.5 μm to 1 μm, and the particle size of inorganic compound C is 4 μm to 5 μm, so that the pore size of the intermediate layer formed by the reaction of inorganic compound B and inorganic compound C is smaller than the pore size of the support layer, the filtration accuracy is higher, and the medium can be further filtered.

[0071] Optionally, the mass of inorganic compound B accounts for 40% to 50% of the total mass of the raw materials of the middle layer, and the mass of inorganic compound C accounts for 40% to 50% of the total mass of the raw materials of the middle layer, so that inorganic compound B and inorganic compound C become the main materials of the middle layer, ensuring the filtering performance of the middle layer.

[0072] Optionally, the inorganic compound B is at least one of α-Al2O3, β-Al2O3, and γ-Al2O3. Preferably, the inorganic compound B is α-Al2O3.

[0073] Optionally, the inorganic compound C is Mg5(CO3)4(OH)2·4H2O, so that the inorganic compound C and the inorganic compound B can be sintered at high temperature to form the main material of the intermediate layer (MgAl2O4 in spinel form), so that the intermediate layer has a higher porosity and good filtering performance.

[0074] Further, step S2 includes:

[0075] S21, adding the dispersant to the solvent and stirring for 10 minutes by ultrasonic vibration;

[0076] S22, adding the inorganic compound B and the inorganic compound C into the solvent at the same time and stirring for 10 minutes by ultrasonic vibration;

[0077] S23, adding the tackifier to the solvent and stirring at 60° C. to 70° C. for 10 minutes by magnetic stirring;

[0078] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0079] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0080] S26. Sinter at a temperature of 1200°C to 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0081] Optionally, in step S2, the solvent is an amphoteric solvent, and the solvent includes one of water, methanol and ethanol. Preferably, the solvent is ethanol.

[0082] Optionally, in step S2, the dispersant is an inorganic dispersant, the dispersant includes one of acetic acid, phosphate, silicate and titanate, and the dispersant is preferably an acetic acid dispersant. The mass of the dispersant accounts for 1% to 2% of the mass of the raw material of the intermediate layer.

[0083] Optionally, in step S2, the thickener is an emulsifier, and the thickener includes one of sodium phosphate, PEG (polyethylene glycol), and hexadecane, and the thickener is preferably PEG. The mass of the thickener accounts for 3% to 5% of the mass of the raw material of the intermediate layer.

[0084] Step S3 is used to prepare the filter layer, and step S3 is further introduced below.

[0085] Optionally, the mass of inorganic compound D accounts for 70% to 75% of the total mass of the raw material of the filter layer, and the mass of inorganic compound E accounts for 25% to 30% of the total mass of the raw material of the intermediate layer, so that inorganic compound D and inorganic compound E constitute the main raw material of the filter layer.

[0086] Optionally, the inorganic compound D is at least one of α-Al2O3, β-Al2O3, and γ-Al2O3. Preferably, the inorganic compound D is α-Al2O3. The inorganic compound E is MgO, so that the inorganic compound D and the inorganic compound E can be sintered at a high temperature to form the main material of the filter layer (MgAl2O4 in the form of spinel), so that the intermediate layer has a higher porosity and good filtering performance.

[0087] Optionally, in step S3, the particle size of the inorganic compound D is 0.1 μm to 0.3 μm, and the particle size of the inorganic compound E is 1 μm to 2 μm, so as to ensure the porosity of the formed filter layer and the filtering accuracy of the filter layer.

[0088] Further, step S3 includes:

[0089] S31, adding the dispersant to the solvent and stirring for 10 minutes by ultrasonic vibration;

[0090] S32, adding inorganic compound D and inorganic compound E to the solvent simultaneously and stirring for 10 minutes by ultrasonic vibration;

[0091] S33, stirring at 60° C. to 70° C. for 10 minutes by magnetic stirring;

[0092] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0093] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0094] S36. Sinter at a temperature of 1200°C to 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample.

[0095] Optionally, in step S3, the solvent is an amphoteric solvent, and the solvent includes one of water, methanol and ethanol, preferably ethanol.

[0096] Optionally, in step S3, the dispersant is an inorganic dispersant, the dispersant includes one of acetic acid, phosphate, silicate and titanate, and the mass of the dispersant accounts for 1% to 2% of the mass of the raw material of the intermediate layer.

[0097] The particle size of the material involved in this application can be obtained through SEM observation, and the porosity of the material can also be calculated through volume density and theoretical density.

[0098] The present application is further described below through specific examples.

[0099] First embodiment

[0100] Step S1:

[0101] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0102] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0103] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0104] S14, finely sifting the solid powder using a 150-mesh sieve;

[0105] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0106] S16. Sintering was performed at 1200° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0107] Step S2:

[0108] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0109] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0110] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0111] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0112] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0113] S26. Use a muffle furnace to sinter at 1200° C. for 2 hours to produce a support layer-intermediate layer sample.

[0114] Step S3:

[0115] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0116] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0117] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0118] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0119] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0120] S36. Use a muffle furnace to sinter at 1200°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 18 μm.

[0121] The scanning electron microscope image of the filter membrane according to the first embodiment is as follows: Figure 1 and Figure 2 shown.

[0122] Second embodiment

[0123] Step S1:

[0124] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0125] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0126] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0127] S14, finely sifting the solid powder using a 150-mesh sieve;

[0128] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0129] S16. Sintering was performed at 1300° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0130] Step S2:

[0131] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0132] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0133] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0134] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0135] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0136] S26. Use a muffle furnace to sinter at 1300° C. for 2 hours to produce a support layer-intermediate layer sample.

[0137] Step S3:

[0138] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0139] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0140] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0141] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0142] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0143] S36. Use a muffle furnace to sinter at 1300°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 20 μm.

[0144] The scanning electron microscope image of the filter membrane according to the second embodiment is as follows: Figure 3 and Figure 4 shown.

[0145] Third embodiment

[0146] Step S1:

[0147] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0148] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0149] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0150] S14, finely sifting the solid powder using a 150-mesh sieve;

[0151] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0152] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0153] Step S2:

[0154] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0155] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0156] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0157] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0158] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0159] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0160] Step S3:

[0161] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0162] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0163] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0164] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0165] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0166] S36. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 19 μm.

[0167] The scanning electron microscope image of the filter membrane according to the third embodiment is as follows: Figure 3 and Figure 4 shown.

[0168] Fourth embodiment

[0169] Step S1:

[0170] S11, add 95g of inorganic compound A (Al2O3, particle size 0.7μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0171] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0172] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0173] S14, finely sifting the solid powder using a 150-mesh sieve;

[0174] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0175] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0176] Step S2:

[0177] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0178] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0179] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0180] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0181] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0182] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0183] Step S3:

[0184] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0185] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0186] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0187] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0188] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0189] S36. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 21 μm.

[0190] Fifth embodiment

[0191] Step S1:

[0192] S11, add 85g of inorganic compound A (Al2O3, particle size 0.7μm), 10g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0193] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0194] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0195] S14, finely sifting the solid powder using a 150-mesh sieve;

[0196] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0197] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0198] Step S2:

[0199] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0200] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0201] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0202] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0203] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0204] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0205] Step S3:

[0206] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0207] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0208] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0209] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0210] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0211] S36. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 18 μm.

[0212] Sixth embodiment

[0213] Step S1:

[0214] S11, add 55g of inorganic compound A (Al2O3, particle size 0.7μm), 40g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0215] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0216] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0217] S14, finely sifting the solid powder using a 150-mesh sieve;

[0218] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0219] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0220] Step S2:

[0221] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0222] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0223] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0224] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0225] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0226] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0227] Step S3:

[0228] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0229] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0230] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0231] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0232] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0233] S36. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 22 μm.

[0234] Seventh embodiment

[0235] Step S1:

[0236] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0237] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0238] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0239] S14, finely sifting the solid powder using a 150-mesh sieve;

[0240] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0241] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0242] Step S2:

[0243] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0244] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0245] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0246] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0247] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0248] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0249] Step S3:

[0250] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0251] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0252] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0253] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0254] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0255] S36. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 31 μm.

[0256] Eighth embodiment

[0257] Step S1:

[0258] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0259] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0260] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0261] S14, finely sifting the solid powder using a 150-mesh sieve;

[0262] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0263] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0264] Step S2:

[0265] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0266] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0267] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0268] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0269] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0270] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0271] Step S3:

[0272] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0273] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0274] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0275] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0276] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0277] S36. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 42 μm.

[0278] Ninth embodiment

[0279] Step S1:

[0280] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0281] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0282] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0283] S14, finely sifting the solid powder using a 150-mesh sieve;

[0284] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0285] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0286] Step S2:

[0287] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0288] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0289] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0290] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0291] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0292] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0293] Step S3:

[0294] S31, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0295] S32, 21 g of inorganic compound D (α-Al2O3, particle size 0.2 μm) and 8.7 g of inorganic compound E (MgO, particle size 1.5 μm) were added to an ethanol solvent at the same time and stirred by ultrasonic vibration for 10 minutes;

[0296] S33, stirring at 65°C for 10 minutes by magnetic stirring;

[0297] S34, immersing the prepared support layer-intermediate layer sample in the solution for 1 minute for coating;

[0298] S35, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0299] S36. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-middle layer-filter layer sample with a filter layer thickness of 57 μm.

[0300] The first comparison

[0301] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0302] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0303] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0304] S14, finely sifting the solid powder using a 150-mesh sieve;

[0305] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0306] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0307] The second comparison

[0308] Step S1:

[0309] S11, add 70g of inorganic compound A (Al2O3, particle size 0.7μm), 25g of corn starch pore former (particle size 2-30μm) and 5g of PVA aqueous solution film-forming aid into a container (volume 100ml) containing ethanol and zirconium oxide balls, and shake well to mix;

[0310] S12, placing the container on a ball mill and rotating it for 24 hours, adjusting the rotation speed to 1 second / revolution;

[0311] S13, using a rotary evaporator to evaporate and dry the inorganic compound slurry after ball milling to prepare a solid powder;

[0312] S14, finely sifting the solid powder using a 150-mesh sieve;

[0313] S15, the finely sieved powder is pressed into a circular sheet of a certain size through a mold and an oil press, the thickness of the circular sheet is 1.5 mm, the pressure is 12 MPa, the pressure is maintained for 1 minute, and a circular sheet with a diameter of 32 mm is made;

[0314] S16. Sintering was performed at 1400° C. for 2 hours using a muffle furnace to produce a support layer sample.

[0315] Step S2:

[0316] S21, adding 0.3 g of acetic acid dispersant to 50 ml of ethanol solvent and stirring for 10 minutes by ultrasonic vibration;

[0317] S22, 14 g of inorganic compound B (α-Al2O3, particle size 0.7 μm) and 14.5 g of inorganic compound C (Mg5(CO3)4(OH)2·4H2O, particle size 4.8 μm) were simultaneously added to an ethanol solvent and stirred by ultrasonic vibration for 10 minutes;

[0318] S23, adding 1.2 g of PEG thickener to the solvent and stirring at 65° C. for 10 minutes by magnetic stirring;

[0319] S24, immersing the prepared support layer in the solution for 1 minute for coating;

[0320] S25, drying the dip-coated sample at 80° C. for 12 hours to volatilize the residual solvent;

[0321] S26. Use a muffle furnace to sinter at 1400°C for 2 hours to produce a support layer-intermediate layer sample.

[0322] After samples of the first to ninth embodiments and the first and second comparative examples were prepared, dust removal efficiency was measured on the samples.

[0323] The dust removal efficiency determination process is as follows:

[0324] Before membrane filtration, the ceramic membrane to be used is dried, and the mass M1 of the membrane and the mass m1 of the paper filter membrane are measured with an electronic balance. After the test, the ceramic membrane and the paper filter membrane are removed, and their masses M2 and m2 are measured respectively, and the mass difference ΔM=M2-M1 and Δm=m2-m1 are calculated. The total dust removal efficiency is calculated as follows: η=ΔM / (ΔM+Δm).

[0325] The dust removal efficiency measurement results and material parameters of various embodiments and comparative examples are shown in Table 1.

[0326] Table 1

[0327]

[0328]

[0329]

[0330] As shown in Table 1, when the sintering temperature is between 1200°C and 1400°C, the thickness of the filter layer is controlled between 18 μm and 57 μm, and the filter membrane has a good total dust removal efficiency. Preferably, the thickness of the filter layer is controlled between 18 μm and 22 μm, and the total dust removal efficiency of the filter membrane can reach 99%. The mass fraction of compound A in the support layer is between 55% and 95%, and the smaller the mass fraction of compound A in the support layer, the higher the porosity of the support layer, and the better the total dust removal efficiency of the filter membrane.

[0331] In addition, compared with the first comparative example, the first to ninth embodiments have an intermediate layer and a filter layer, and the overall dust removal efficiency is higher. Compared with the second comparative example, the first to ninth embodiments have a filter layer, and the overall dust removal efficiency is also higher.

[0332] In summary, the filter membrane prepared according to the filter membrane preparation method of the present application has good filtering performance and dust removal efficiency.

[0333] The present application also provides a filtering device, comprising the filtering membrane according to the above. The filtering device according to the present application has low cost, good pore-forming performance, and good filtering performance as well as good mechanical properties.

[0334] Unless otherwise defined, the technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of this application. The terms used herein are only for describing specific implementation purposes and are not intended to limit this application. Terms such as "setting" appearing in this article can mean that one component is directly attached to another component, or that one component is attached to another component through an intermediate. Features described in this article in one embodiment may be applied to another embodiment alone or in combination with other features, unless the feature is not applicable in the other embodiment or otherwise specified.

[0335] The present application has been described through the above-mentioned embodiments, but it should be understood that the above-mentioned embodiments are only for the purpose of example and description, and are not intended to limit the present application to the described embodiments. It can be understood by those skilled in the art that more variations and modifications can be made according to the teachings of the present application, and these variations and modifications all fall within the scope of protection claimed in the present application.

Claims

1. A filter membrane, characterized in that: The filter membrane comprises: Support layer; an intermediate layer, the intermediate layer being disposed on one side surface of the support layer in the thickness direction and comprising a spinel material; and The filter layer is arranged on a surface of the intermediate layer facing away from the support layer and comprises a spinel material. The porosity of the filter layer is smaller than the porosity of the intermediate layer.

2. The filtration membrane according to claim 1, characterized in that The spinel material of the intermediate layer and / or the filter layer is MgAl2O4.

3. The filtration membrane according to claim 1, characterized in that The filter layer has a thickness of 15 μm to 57 μm.

4. The filtration membrane according to claim 3, characterized in that The filter layer has a thickness of 15 μm to 25 μm.

5. The filtration membrane according to claim 1, characterized in that The support layer includes an inorganic compound A, and the mass of the inorganic compound A accounts for 55% to 95% of the mass of the support layer.

6. The filtration membrane according to claim 5, characterized in that The inorganic compound A includes one or more of alumina, zirconium dioxide, titanium dioxide and zeolite.

7. The filtration membrane according to claim 1, characterized in that The thickness of the support layer is at least 1.5 mm.

8. The filtration membrane according to claim 1, characterized in that The porosity of the intermediate layer is smaller than the porosity of the support layer.

9. The filtration membrane according to claim 1, characterized in that The thickness of the filter layer is smaller than the thickness of the support layer.

10. A method for preparing a filtration membrane, characterized in that: include: S1, sintering the inorganic compound A to form a support layer; S2, dip-coating the inorganic compound B and the inorganic compound C onto the support layer and then sintering them, thereby forming an intermediate layer on the surface of the support layer; S3, dip-coating the inorganic compound D and the inorganic compound E onto the intermediate layer and then sintering the intermediate layer to form a filter layer on the surface of the intermediate layer.

11. The method for preparing a filtration membrane according to claim 10, characterized in that: In step S1, step S2 and step S3, the sintering temperature is 1200°C to 1400°C.

12. The method for preparing a filtration membrane according to claim 10, characterized in that: The step S1 comprises: The inorganic compound A, the pore former and the film-forming aid are ball-milled, dried and sieved to obtain a solid powder; The support layer is obtained by tableting and sintering the solid powder.

13. The method for preparing a filtration membrane according to claim 10, characterized in that: The mass of the inorganic compound B accounts for 40% to 50% of the total mass of the intermediate layer raw material, and the mass of the inorganic compound C accounts for 40% to 50% of the total mass of the intermediate layer raw material; and / or The inorganic compound B includes one or more of α-Al2O3, β-Al2O3, and γ-Al2O3, and the inorganic compound C is Mg5(CO3)4(OH)2·4H2O.

14. The method for preparing a filtration membrane according to claim 10, characterized in that: The mass of the inorganic compound D accounts for 70% to 75% of the total mass of the raw material of the filter layer, and the mass of the inorganic compound E accounts for 25% to 30% of the total mass of the raw material of the intermediate layer; and / or The inorganic compound D is at least one of α-Al2O3, β-Al2O3, and γ-Al2O3, and the inorganic compound E is MgO.

15. A filtering device, characterized in that: Comprising the filtration membrane according to any one of claims 1 to 9.